Pengaruh Kepribadian, Kompetensi, Motivasi Kerja dan Pengembangan Karir Terhadap Kepuasan Kerja Tenaga Kesehatan Rumah Sakit JIH Purwokerto - Anggi Nur Aisah; Purnadi Purnadi; Fatmah Bagis; Dian Widyaningtyas (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of personality, competence, work motivation, and career development on job satisfaction among healthcare workers at JIH Purwokerto Hospital. This study used a quantitative approach with a non-probability sampling method and a saturated sampling technique, involving 127 healthcare workers. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression, the F-test, and the t-test using SPSS software. The t-test results indicated that personality and work motivation variables had a positive and significant effect on job satisfaction. Conversely, competency and career development variables were found to have no significant effect on job satisfaction among the study subjects. Simultaneously (F-test), all independent variables influenced job satisfaction with a coefficient of determination of 43.1%. Healthcare worker job satisfaction at JIH Purwokerto Hospital was more dominantly influenced by psychological and motivational factors (personality and motivation) than technical or structural aspects (competence and career). Hospital management is advised to continue strengthening character development and creating a supportive work environment to maintain the stability of healthcare workers' motivation and job satisfaction.